2010
DOI: 10.2113/econgeo.105.5.873
|View full text |Cite
|
Sign up to set email alerts
|

P-T-X Conditions of Fluids in the Sunrise Dam Gold Deposit, Western Australia, and Implications for the Interplay between Deformation and Fluids

Abstract: The Late Archean Sunrise Dam gold deposit (~10 Moz) is hosted within greenschist-facies rocks and is characterized by extreme structural complexity, resulting from a protracted deformation history with evidence of structural reactivation and multiple phases of gold mineralization. Early Group I orebodies are hosted within shallow-to moderately dipping northwest-trending shear zones and occur in foliation parallel veins within a strong penetrative fabric. Group II orebodies occur within steeply dipping shear zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…It should be noted that the numerical models presented here were not intended to predict the deposit-scale characteristics of the Sunrise Dam and Wallaby gold deposits, due to the lack of structural and lithological detail in the model at the deposit scale. Taking the Sunrise Dam deposit, for example, Baker et al (2010) presented a detailed deposit-scale structural and geochemical study and concluded that the deposit is characterized by extreme structural complexity. They showed that three groups of orebodies within the deposit are hosted by three different structures: (i) shallow to moderately dipping shear zones; (ii) steeply dipping shear zones; and (iii) stockwork veins.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the numerical models presented here were not intended to predict the deposit-scale characteristics of the Sunrise Dam and Wallaby gold deposits, due to the lack of structural and lithological detail in the model at the deposit scale. Taking the Sunrise Dam deposit, for example, Baker et al (2010) presented a detailed deposit-scale structural and geochemical study and concluded that the deposit is characterized by extreme structural complexity. They showed that three groups of orebodies within the deposit are hosted by three different structures: (i) shallow to moderately dipping shear zones; (ii) steeply dipping shear zones; and (iii) stockwork veins.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of previous studies of the Sunrise Dam system with a focus on both structural aspects (see references in Blenkinsop et al 2007) and ore fluid chemistry (Brown et al 2003;Blenkinsop et al 2007;Baker et al 2010). Using a summary of previous and new fluid inclusion data integrated with structural models, Baker et al (2010) concluded that gold at Surnise Dam was precipitated as a result of un-mixing of CO 2 -H 2 O-Cl fluids during deformation-driven depressurization from supralithostatic to hydrostatic pressures by failure across shear zones.…”
Section: Fluids and Structuresmentioning
confidence: 99%
“…Using a summary of previous and new fluid inclusion data integrated with structural models, Baker et al (2010) concluded that gold at Surnise Dam was precipitated as a result of un-mixing of CO 2 -H 2 O-Cl fluids during deformation-driven depressurization from supralithostatic to hydrostatic pressures by failure across shear zones. They conclude that this led to gold deposition in steep cross-cutting vein and breccia systems, also arguing that this process was overprinted by mineralization from a later, CO 2 -rich fluid that was driven along preferential flow paths such as porphyry dyke margins, giving rise to later high-grade gold.…”
Section: Fluids and Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…These HSs is rich in aromatic carbon, phenolic structures, and conjugated double bonds [4]. For a long time, these peat soil HSs have been claimed to have important roles in Au transport and/or fixation during the formation of laterites [5][6]. Humic substances have also been found to be associated with Au anomalies in stream sediments and soils [7].…”
Section: Introductionmentioning
confidence: 99%